1995
DOI: 10.1007/bf00410192
|View full text |Cite
|
Sign up to set email alerts
|

The response of adult and developing rat plantaris muscle to overload

Abstract: The effect of overload on the rat plantaris muscle was studied in animals of different ages. Overload was induced by removal of gastrocnemius and soleus muscles. As expected, when the operation was carried out in adults, the plantaris muscle became heavier and stronger. These changes occured within 30 days after the operation. In animals in which the operation was carried out 1-12 days after birth and the muscle examined 6-20 weeks later, different results were obtained. In the group operated at 1-9 days of ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
2
0
1
Order By: Relevance
“…The finding of higher TetF values in this study for all MU types of overloaded MG was in accordance with earlier observations . Olha et al .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The finding of higher TetF values in this study for all MU types of overloaded MG was in accordance with earlier observations . Olha et al .…”
Section: Discussionsupporting
confidence: 94%
“…The results summarized in Table indicate that notable overload effects were induced in the MG muscle, as the majority of basic MU properties were modified in accordance with previous observations . Effects of the 3‐month compensatory overload affected all MU types, but the most noticeable were in relation to FR units.…”
Section: Resultssupporting
confidence: 88%
“…Although this con®rms the results found in previous studies using other methods of overload (Ianuzzo et al 1976;Baldwin et al 1982;Timson et al 1985;Frischknecht and Vrbova 1991;Frischknecht et al 1995;Yamaguchi et al 1996), the reported increase in muscle mass observed in these studies was larger than that observed in the present work. This may be due to the difference in application of the overload: in the present work, the load was applied to the whole hindlimb and all muscles were kept intact; thus a large portion of the overload was carried by other muscles, and in particular by gastrocnemius muscle.…”
Section: Selective Hypertrophy Of the Soleus Musclecontrasting
confidence: 58%